2020
DOI: 10.2147/dmso.s263093
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association of Metabolic Syndrome and Its Components with Electrocardiogram Parameters and Abnormalities Among an Iranian Rural Population: The Fasa PERSIAN Cohort Study</p>

Abstract: Background: Metabolic syndrome (MetS) as a set of cardiac risk factors and its growing prevalence is one of the major concerns in different societies. In this study, we aimed to investigate the relationship between Mets and electrocardiogram (ECG) parameters and abnormalities as indicators for subclinical cardiovascular diseases (CVD). Methods: In this sub-analysis study, we used the data from Fasa PERSIAN Cohort Study which includes subjects age 35-70 years. Subjects with available ECG data included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Waist circumference, one of the widely used criteria for metabolic syndrome, is one of the most common determinants of ECG changes and hypertension. Abdominal obesity raises the diaphragm, resulting in increased sympathetic activity and cardiac output, thereby affecting the ECG parameters [ 25 , 26 ]. An Asian cohort showed that the participants with higher BMIs had a longer PR interval, wider QRS, a more negative QRS axis, and a larger RaVL [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Waist circumference, one of the widely used criteria for metabolic syndrome, is one of the most common determinants of ECG changes and hypertension. Abdominal obesity raises the diaphragm, resulting in increased sympathetic activity and cardiac output, thereby affecting the ECG parameters [ 25 , 26 ]. An Asian cohort showed that the participants with higher BMIs had a longer PR interval, wider QRS, a more negative QRS axis, and a larger RaVL [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a clear understanding of the precise mechanisms linking NAFLD to impaired CANS function remains elusive. The most obvious explanation for our findings is that NAFLD is associated with CANS dysfunction simply as a consequence of the shared cardiometabolic risk factors (for example, obesity, insulin resistance, T2DM, or low-grade chronic inflammation, which are also known risk factors for impaired CANS function [40][41][42]). However, it should be noted that in our study NAFLD was associated with cardiac sympathetic/parasympathetic imbalance, independent of T2DM status, and other shared cardiometabolic risk factors (such as BMI, hypertension, dyslipidemia, HOMA-IR score, and plasma CRP levels).…”
Section: Discussionmentioning
confidence: 85%
“…Waist circumference has been one of the widely used criteria for metabolic syndrome, which is one of the most common determinants of ECG changes along with hypertension among these people. Abdominal obesity raises the diaphragm, resulting in increased sympathetic activity and cardiac output, thereby affecting the ECG parameters (25).…”
Section: Discussionmentioning
confidence: 99%